Troubleshooting of Von Karman Induced Penstock Protection Valve Resonance at FMHL+. (December 2019) - Nicolet, C; Alligné, S; Furrer, M; Fischer, D; Grognuz, J; Chène, O; Valluy, B
Abstract: The FMHL power plant was originally a 240 MW pumped-storage power plant in Switzerland, put in operation in 1971 which installed capacity was extended to 480 MW in 2016 with maximal output power set to 420 MW including 60 MW as reserve. The significant increase of the total discharge of the power plant in generating mode from 32 m 3 /s at 240 MW to 57 m 3 /s at 420 MW might be critical due to the higher flow velocity throughout the different safety valves of the power plant. During commissioning, the discharge was increased stepwise from 32 to 57 m 3 /s while monitoring the vibration of the safety valves. Significant vibration amplitudes have been recorded at a frequency of 62.5 Hz on the penstock protection valve for a discharge of 43 m 3 /s. Von Karman vortex shedding induced resonance on the stiffener of the bi-plan valve obturator was then suspected. The paper presents troubleshooting of this resonance problem, where CFD and FEM investigations have been performed to define appropriate trailing edge modifications of the obturator stiffener plates able to significantly reduce the Von Karman dynamic lift coefficient and thus reduce drastically vibration amplitudes.